Guidelines on the irritable bowel syndrome: mechanisms and practical management. Issue 12 (8th May 2007) - Spiller, R; Aziz, Q; Creed, F; Emmanuel, A; Houghton, L; Hungin, P; Jones, R; Kumar, D; Rubin, G; Trudgill, N; Whorwell, P
Abstract : Background: IBS affects 5–11% of the population of most countries. Prevalence peaks in the third and fourth decades, with a female predominance. Aim: To provide a guide for the assessment and management of adult patients with irritable bowel syndrome. Methods: Members of the Clinical Services Committee of The British Society of Gastroenterology were allocated particular areas to produce review documents. Literature searching included systematic searches using electronic databases such as Pubmed, EMBASE, MEDLINE, Web of Science, and Cochrane databases and extensive personal reference databases. Results: Patients can usefully be classified by predominant bowel habit. Few investigations are needed except when diarrhoea is a prominent feature. Alarm features may warrant further investigation. Adverse psychological features and somatisation are often present. Ascertaining the patients' concerns and explaining symptoms in simple terms improves outcome. IBS is a heterogeneous condition with a range of treatments, each of which benefits a small proportion of patients. Treatment of associated anxiety and depression often improves bowel and other symptoms. Randomised placebo controlled trials show benefit as follows: cognitive behavioural therapy and psychodynamic interpersonal therapy improve coping; hypnotherapy benefits global symptoms in otherwise refractory patients; antispasmodics and tricyclic antidepressants improve pain; ispaghula improves pain and bowel habit; 5-HT3 antagonists improve global symptoms, diarrhoea, and pain but may rarely cause unexplained colitis; 5-HT4 agonists improve global symptoms, constipation, and bloating; selective serotonin reuptake inhibitors improve global symptoms. Conclusions: Better ways of identifying which patients will respond to specific treatments are urgently needed.